2014
DOI: 10.2147/vmrr.s59609
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the clinical and analgesic effects of subarachnoid ketamine-lidocaine administration in goats undergoing mastectomy

Abstract: Twenty adult female goats affected with chronic mastitis were subjected to mastectomy or hemimastectomy under subarachnoid regional analgesia using a ketaminelidocaine combination. Ketamine at 1.5 mg/kg and lidocaine hydrochloride at 1.25 mg/kg were administered intrathecally at the lumbosacral intervertebral space. Goats were then subjected to a 120-minute observation period for systemic or neurotoxic symptoms such as agitation, restlessness, hind limb paralysis, or seizures. In addition, analgesia of the cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…No significant differences or abnormalities in temperature, heart and respiratory rates were observed among times inside each experimental group or between groups ( Table 1 ). This is in accordance with previous results ( Daradka & Ismail, 2014 ; De Rossi, Junqueira, Lopes & Beretta, 2005 ). None of the animals presented regurgitation or ruminal bloating.…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…No significant differences or abnormalities in temperature, heart and respiratory rates were observed among times inside each experimental group or between groups ( Table 1 ). This is in accordance with previous results ( Daradka & Ismail, 2014 ; De Rossi, Junqueira, Lopes & Beretta, 2005 ). None of the animals presented regurgitation or ruminal bloating.…”
Section: Resultssupporting
confidence: 94%
“…Subarachnoid anesthesia protocol used in this study promoted surgical analgesia, allowing 100% of bilateral recumbent orchiectomies with only mild sedation of the animals, without changing cardiorespiratory parameters, promoting regurgitation or bloating. Daradka and Ismail (2014) showed that RS-ketamine at 1.5 mg/kg and lidocaine at 1.25 mg/kg administered intrathecally at the lumbosacral intervertebral space provided safe and effective analgesia of the caudal abdominal and udder region sufficient to perform mastectomy or hemimastectomy in goats. However, the animals delayed 15 min to reach the maximal analgesia and presented significant rise in heart rate at some point between 5 and 90 min.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation